Knowledge, attitudes, and practices regarding cervical cancer screening among women in metropolitan Lima, Peru: a cross-sectional study - Michelle M. Pieters; Rae Jean Proeschold-Bell; Emily Coffey; Megan J. Huchko; Lavanya Vasudevan (BMC, 2021)
Abstract Background Cervical cancer is a leading cause of cancer deaths among women of reproductive age in Peru. Screening and early identification of pre-cancerous lesions are a cornerstone of the cervical cancer prevention strategy. Yet, there is limited literature on barriers to screening among Peruvian women. In this cross-sectional study, we aimed to examine Peruvian women's knowledge, attitudes, and practices regarding cervical cancer screening and identify possible reasons for the gap between knowledge and screening. Methods The study was conducted in metropolitan Lima from June-August 2019. We purposefully recruited 12 women who had previously been screened, and 12 who had never been screened for cervical cancer. The women completed a 40-question knowledge and attitude survey and an in-depth interview about barriers to screening. Descriptive analysis was used to calculate a knowledge and attitude score and qualitative analysis was guided by the Health Belief Model constructs. Results Previously screened participants had greater knowledge of cervical cancer symptoms, risk factors, and prevention (mean score = 28.08, S.D. = 4.18) compared to participants who had never been screened (mean score = 21.25, S.D. = 6.35). Both groups described lack of priority and embarrassment as barriers to cervical cancer screening. For participants who had never been screened before, major barriers included the fear of a cancer diagnosis and lack of information about screening services. Pregnancy, unusual gynecological symptoms and encouragement from friends and family were cues to action for participants seeking screening. Most participants in both groups recognized the benefits of getting screened for cervical cancer. Being previously screened increased participants' self-efficacy for engaging in screening behaviors again. Misconceptions regarding screening procedures and cervical cancer were also noted as barriers for participants accessing screening services. Conclusions Improving knowledge and awareness about cervical cancer and screening programs may improve screening behaviors among women. Targeting women who have never been screened before and addressing their fears and concerns around embarrassment may be other areas for intervention. Misconceptions that deter women from screening services are an important issue that should be addressed in order to increase the number of women who get timely screenings.